Pulmonary Hyalinizing Granuloma With Elevated IgG4 Levels, A Link To IgG4-Related Sclerosing Disease? (Archives of Clinical and Medical Case Reports, 2021)
Pulmonary Hyalinizing granuloma (PHG) is a rare form of lung pathology, often initially presenting as nodules prompting workup for possible malignancy. We present a case of a 29-year-old man with an irregularly shaped, growing hilar mass, suggested to be PHG on initial biopsy, later confirmed by surgical pathology examination of the entire lung after pneumonectomy. The pathology findings also reported many of the histopathologic features found in IgG4-related sclerosing disease (ISD). This gross presentation and the correlation with ISD may have therapeutic implications in the management of PHG.